2007
DOI: 10.1038/sj.ejhg.5201896
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for molecular karyotyping in constitutional genetic diagnosis

Abstract: Array-based whole genome investigation or molecular karyotyping enables the genome-wide detection of submicroscopic imbalances. Proof-of-principle experiments have demonstrated that molecular karyotyping outperforms conventional karyotyping with regard to detection of chromosomal imbalances. This article identifies areas for which the technology seems matured and areas that require more investigations. Molecular karyotyping should be part of the genetic diagnostic work-up of patients with developmental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 68 publications
0
105
0
12
Order By: Relevance
“…However, more recent studies have already mentioned the partial replacement of conventional karyotyping by molecular karyotyping. 53,57 In addition, Koolen et al 29 described a workflow for the clinical interpretation of CNVs in individuals with MR. Our results show that high-density SNP arrays can be successfully used as a tool for the detection of CNVs, low-level mosaicism and copy number neutral abnormalities. Their high resolution and commercial availability make them attractive to implement in a routine diagnostic setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have already mentioned the partial replacement of conventional karyotyping by molecular karyotyping. 53,57 In addition, Koolen et al 29 described a workflow for the clinical interpretation of CNVs in individuals with MR. Our results show that high-density SNP arrays can be successfully used as a tool for the detection of CNVs, low-level mosaicism and copy number neutral abnormalities. Their high resolution and commercial availability make them attractive to implement in a routine diagnostic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, small CNVs with an average length of several Kbs cover about 12% of the normal human genome, 11 and it is difficult to assess whether they have any clinical consequence. 30 To optimize the management of CNV analyses, a workflow for clinical practice was published by Koolen et al 24 In our study, these guidelines were followed to further select the most likely pathogenic CNVs, and it was shown that more than 80% of CNVs detected by high-resolution platforms were polymorphic, nonpathogenic copy number changes. In particular, we found that 100% of CNVs showing a length lower than 100 Kb completely overlapped to polymorphic genomic regions.…”
Section: Discussionmentioning
confidence: 99%
“…These are discussed in more detail below. Quality criteria for genomic arrays have been published [Fiegler et al, 2006;Vermeesch et al, 2005Vermeesch et al, , 2007. These recommendations were based on the use of bacterial artificial chromosome arrays, but the general principles apply to oligonucleotide and SNP arrays too.…”
Section: Analytical Validitymentioning
confidence: 99%